Fragility fractures and reversible osteopaenia due to chronic hyponatraemia in an adolescent male. Issue 7 (27th July 2019) - Patel, Mital; Ayus, Juan Carlos; Moritz, Michael L
Abstract : Fragility fractures are common in older adults and rare in children. Recent studies have demonstrated that hyponatraemia is a novel risk factor for the development of osteoporosis and hip fractures in older people. Animal studies suggest that hyponatraemia can lead to decreased bone mineral density by stimulating osteoclastic activity in order to mobilise sodium from the bone. Reported is a 16-year-old man with intractable epilepsy and an 11-year history of chronic hyponatraemia (126–135 mEq/L) due to valproic acid induced syndrome of inappropriate antidiuresis who sustained low-impact fragility fractures and had evidence of osteopaenia on both X-ray and dual energy X-ray absorptiometry (DEXA). Hyponatraemia resolved following the discontinuation of valproic acid and bone mineral density normalised on a repeat DEXA 19 months later. This case provides evidence supporting the contention that chronic hyponatraemia contributes to osteopaenia and fragility fractures and that the bone abnormalities are potentially reversible following the correction of hyponatraemia.